Post-Pandemic Shift in Procurement Behavior: Evidence from Logistics Service Selection in the Chemical Industry - Ristona Widoretno; Teuku Yuri M Zagloel (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Logistics has become increasingly critical in maintaining supply chain stability, particularly in industries such as chemicals where operations involve higher levels of complexity and risk. The disruptions experienced during the COVID-19 pandemic—ranging from transportation delays to cost fluctuations—have not only affected operational performance but also influenced how companies evaluate logistics service providers (LSPs). This study explores how procurement priorities have shifted in response to these changes. By combining the Analytical Hierarchy Process (AHP) and SERVQUAL, the research attempts to capture both what customers consider important and how they perceive actual service performance. The study was conducted at a logistics service provider in Indonesia serving the chemical industry. The findings suggest that assurance, reliability, and responsiveness have become more important than cost in selecting LSPs. However, these same dimensions also show the largest performance gaps. This indicates that, although expectations have changed, service delivery has not fully kept pace. The results highlight the need for logistics providers to adjust their service approach in a more consistent and customer-oriented manner.